Factors influencing population dynamics of five antelope species in Ruma National Park, Kenya - Johnstone , Kimanzi, K.; Jennifer , Wanyingi, N.; Hellen , Ipara; O. Paul, Odwori, (African Journal of Education,Science and Technology (AJEST), 2016)
Establishing and understanding causal influences on population dynamics of wildlife is essential prerequisite to formulate effective wildlife conservation strategies. This paper investigates how five antelope species (topi, oribi, impala, reedbuck and hartebeest) respond to changes in wildlife habitat, rainfall and competition with other grazers in Ruma National Park (RNP) using data for the past over 30 years (1976 – 2008). Data on habitat change were obtained by analyzing multi-temporal Landsat images from 1973 to 2005. Data on rainfall and population estimates of antelopes were obtained from park records from 1976 to 2008. Data were analyzed using diverse methods including correlation, linear regression and negative binomial regression. Regression analysis showed an overall insignificant increase in topi population, significant decline in the populations of impalas (R2 = 0.506, p = 0.042), and insignificant decline in the populations of reedbuck, hartebeest and oribi. Modelling using negative binomial regression showed that the population changes of different antelopes were attributed to different factors except the Oribi whose decline could not be explained by any of the factors considered in this study. The population increase of topi was due to its preference of drier savannah habitat and low rainfall that prevailed in RNP. The population decline of impalas was attributed to decrease in rainfall and habitat change. The population decline of reedbuck was partly due to competition with topi and habitat destruction and degradation through uncontrolled burning and occurrence of droughts that dry out the preferred wetland habitats. The population decline of hartebeest was mainly due to competition with topi. Therefore, there is need to implement management interventions such as prescribed burning, artificial provision of water and translocation of topi to halt further population decline and prevent possible local extinction of affected antelopes in the park.